Highly efficient electrochemiluminescence based on pyrazolecarboxylic metal organic framework. Issue 12 (17th February 2016) - Feng, Chao; Ma, Yu-Heng; Zhang, Duo; Li, Xue-Jing; Zhao, Hong
Abstract : A series of transition metal complexes with the ligands 3-pyrazoledicarboxylic acid (H2 L 1 ) and ethyl 1-(2-ethoxy-2-oxoethyl)-1 H -pyrazole-3-carboxylate (epzc) have been synthesized. Abstract : A series of transition metal complexes with the ligands 3-pyrazoledicarboxylic acid (H2 L 1 ) and ethyl 1-(2-ethoxy-2-oxoethyl)-1 H -pyrazole-3-carboxylate (epzc) have been synthesized. The epzc generated 1-(carboxymethyl)-1 H -pyrazole-3-carboxylic acid (H2 L 2 ) by an in situ hydrothermal hydrolysis reaction, using a one-pot method. Simple mononuclear [Co(HL 1 )2 (H2 O)2 ] (1 ) and [Ni(L 2 )(H2 O)4 ] (4 ), dinuclear [Ni2 (L 1 )2 (H2 O)6 ]·H2 O (2 ) and [Cu2 (L 2 )2 (H2 O)4 ] (5 ) and 2D frameworks [Cu2 (L 1 )2 ] n (3 ), [Co2 (L 2 )2 (H2 O)4 ] n (6 ) have been isolated. The structures have been established by single-crystal X-ray diffraction, and the complexes characterized by FT-IR, thermogravimetric analysis (TGA), PRXD, UV–Vis spectroscopy, and fluorescent spectroscopy.1, 2, 4 and5 were further assembled to form a supramolecular structure by hydrogen-bonding interactions and/or π⋯π stacking.3 and6 both possess a 2D network structure that is further interlinked via intermolecular hydrogen-bonding interactions. Most importantly, the complexes demonstrated highly intense electrochemiluminescence (ECL) in DMF solution.